FORMULASI DAN UJI STABILITAS FISIK SERTA PENENTUAN NILAI SPF (Sun Protecting Factor) GEL MOISTURIZER EKSTRAK ETANOL DAUN KELAKAI (Stenochlaena Palustris (BURM. F.) Bedd.) - Sembiring, Pintata (Jurnal Penelitian Farmasi Dan Herbal, 2025)
Flavonoids in kelakai (Stenochlaena palustris) leaves function as powerful antioxidants that increase skin protection against UV radiation through absorption and scattering of ultraviolet rays. The presence of chromophore groups in the form of conjugated double bonds in flavonoids is able to absorb UVB rays so as to reduce their intensity on the skin and contribute to increasing the Sun Protection Factor (SPF) value of the moisturizer gel. This allows the product to function as a moisturizer as well as a natural plant-based sunscreen. This research aims to formulate kelakai leaf extract moisturizer gel, eval_uate its physical stability, and measure the SPF value. The extract was obtained through maceration, then made into moisturizer gel with concentrations of 3% (F1), 5% (F2), and 7% (F3). For four weeks, organoleptic, homogeneity, spreadability, pH, stability, viscosity, and centrifugation tests were conducted. The results showed that all formulas were homogeneous, brownish yellow (F1), light brown (F2), and dark brown (F3) in color; spreadability 5.39-6.20 cm; pH 5.07-5.96; stable at room temperature and cold; viscosity 6192-7108 cPs; and no phase separation. In vitro SPF measurements using a UV-Vis spectrophotometer at a wavelength of 290-320 nm showed the highest SPF value in F3 (7% extract) of 27.51, while F1 and F2 were 18.49 and 21.94 respectively, so that the three formulas can provide optimal protection from UV rays.